2016
DOI: 10.3389/fneur.2016.00201
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Magnetic Resonance Imaging Study of Head Movements in Cervical Dystonia

Abstract: Cervical dystonia (CD) is a neurological disorder characterized by abnormal movements and postures of the head. The brain regions responsible for these abnormal movements are not well understood, because most imaging techniques for assessing regional brain activity cannot be used when the head is moving. Recently, we mapped brain activation in healthy individuals using functional magnetic resonance imaging during isometric head rotation, when muscle contractions occur without actual head movements. In the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 58 publications
7
32
0
Order By: Relevance
“…Supporting the notion that CD is a network disorder [Battistella et al, 2017;Lehericy et al, 2013;Neychev et al, 2011;Prudente et al, 2014], the observed functional alterations of intra-and inter-regional measurements are consistent with previous studies reporting a wide distribution of structural [Prell et al, 2013;Ramdhani et al, 2014] and functional [de Vries et al, 2008;Prudente et al, 2016] alterations in the basal ganglia, thalamus, cerebellum, sensorimotor cortex, and other cortical regions. Particularly, a previous review [Neychev et al, 2011] has pointed out that dystonia may result from combined dysfunction of multiple nodes or from aberrant communications among them; but which of these possibilities best applies to dystonia remains unclear.…”
Section: Discussionsupporting
confidence: 90%
“…Supporting the notion that CD is a network disorder [Battistella et al, 2017;Lehericy et al, 2013;Neychev et al, 2011;Prudente et al, 2014], the observed functional alterations of intra-and inter-regional measurements are consistent with previous studies reporting a wide distribution of structural [Prell et al, 2013;Ramdhani et al, 2014] and functional [de Vries et al, 2008;Prudente et al, 2016] alterations in the basal ganglia, thalamus, cerebellum, sensorimotor cortex, and other cortical regions. Particularly, a previous review [Neychev et al, 2011] has pointed out that dystonia may result from combined dysfunction of multiple nodes or from aberrant communications among them; but which of these possibilities best applies to dystonia remains unclear.…”
Section: Discussionsupporting
confidence: 90%
“…3A). Medial and lateral clusters were found within the somatosensory cortex, consistent with previous reports of both a medial and lateral representation for the neck within the homunculus (Prudente et al, 2015(Prudente et al, , 2016. Some smaller clusters of (positive and negative) functionally connected voxels were also present ( Supplementary Fig.…”
Section: Lesion Network Mappingsupporting
confidence: 90%
“…Our cerebellar and somatosensory regions of interest were used as seed regions to compare functional connectivity patterns between 39 idiopathic cervical dystonia patients and 37 control subjects, in a dataset collated from two previously published rs-fcMRI studies of idiopathic cervical dystonia (Delnooz et al, 2013;Prudente et al, 2016). The preprocessing of the rs-fcMRI data followed conventional methods and guidelines, including global signal regression (Fox et al, 2010;Murphy et al, 2016), but added an extra artefact-reduction step modified from prior principal component analysis-based approaches (Behzadi et al, 2007)…”
Section: Relevance To Idiopathic Cervical Dystoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the increased severity of dystonic symptoms was associated with reduced functional activity in S1 and increased functional activity in the anterior portion of the cerebellum. A recent fMRI study in CD revealed that head rotation in the direction of dystonic head rotation is related to hyperactivity in the anterior cerebellum and that head rotation in the opposite direction is associated with increased activity in the sensorimotor cortex [Prudente et al, 2016]. Together, these findings reinforce the view that both cortical and subcortical sensorimotor abnormalities are likely to contribute to dystonic symptoms in this patient population [Løkkegaard et al, 2016;Prudente et al, 2014], and both S1 and cerebellum could be targets for intervention in studies looking for ways to reduce symptoms in CD.…”
Section: Discussionmentioning
confidence: 99%